Bewertungsspiele: von der Handlungs- zur Koordinationstheorie - Stachura, Mateusz (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2017)
Unsolved problems in the theory of action spread at the level of the coordination social activities. If action theories work with shortened “models of man” also the answers to questions about the possibility of social order, of hierarchie and of the cooperation on the market fall short of requirements. Goal attainment and social recognition are two widely disparate theoretical cornerstones on which hitherto separate theoretical buildings were raised. By contrast, a concept of the social game, which should be introduce here, connects the both moments: Games are goal-oriented interactions in which people recognize themselves mutually. The game player can recognize each other only in the sense that the game is normative regulated. The goal-orientation is thus normative broken. The social recognition is, however, relateled to and relativized by the game success. The theorem of the social game offers solutions to the problem of action coordination in the hierarchy and on the market.
Gesehen am 09.08.2018